Design and implementation of asynchronous low power sub-threshold memory circuit - Khor, Boon Pin. (2009)
This project presents the design and implementation of a low-power asynchronous memory circuit operating in subthreshold region down to 0.2V. The memory circuit will be employed in a low-power asynchronous subthreshold FIR filter.